ScanMed: a mobile medicine adherence application with intake validation using QR code - Mohd Nor, Rizal; Mohamadali, Noor Azizah; Azmi, Khairul; Marzuki, Ahmad; Mohd Nor, Leilanie; Yusof, Mohar (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The impact of medication adherence is proven to affect hospitalization risk and healthcare cost. In Malaysia, failure in taking medication as prescribed is a complicated and common problem. There are many reasons people fail to take their medication as prescribed. Some of the few common issues are remembering to consume their medicine timely, doubts in medication effectiveness, concerns on side effects or having difficulty in taking the medication (especially with injections or inhalers) and rising cost of prescribed medications. Tracking patient medication intake leads to many advantages, one of which is lower medication due to adherence, health-care cost which effects insurance coverage premiums. In this paper, we develop an application to track medication using a smart phone and the use of QR code. Each medication transaction requires a proof of work to signify that the user have taken their medication at the correct date and time. A QR-Code reader will be used to capture medication taken printed on medication labels and each scan is considered as a proof of work . Our contribution is to create a mobile application that can help track medication intake, as well as remind, inform and warn users about the medication that they are taking.